Analysis of the Role of the Regional Inspectorate in the Budget Management Review on the Implementation of the Deli Serdang Regency APBD - Putri Gusniati; Nur Rahmadi Bi Rahmani (Journal of Indonesian Management, 2022)
Regional autonomy is a breath of fresh air for the region, because it not only gets greater authority but also allocates a larger budget. The source of regional expenditure comes from regional original income from transfer of funds, regional original income and other legal sources. Most regional income donations come from balancing funds with a trend that continues to shrink. The research procedure used is a qualitative research procedure. The method of collecting information used is observation and interviews. The results of the research obtained in an effort to improve the welfare of citizens, regional governments are faced with the need for shopping areas which continues to increase while the original source of income for the region is limited. If the government is not able to maximize income outside the balancing fund, it can enlarge the fiscal gap that continues to be large. This is in line with the role of the inspectorate in carrying out a budget review for the implementation of the APBD in Deli Serdang Regency.